Management of Impacted Premolar With Root Dilaceration Caused by Radicular Cyst in Deciduous Molar: A Case Report - Shuhao Xu; Xiaolong Li; Yu Zhang; Wei Li (Case Reports in Dentistry, 2025)
Radicular cyst is the most common inflammatory odontogenic cyst in the oral cavity, but it rarely occurs in deciduous teeth. Radicular cysts in deciduous teeth can lead to root dilaceration in permanent successor teeth, resulting in impacted permanent teeth. We presented an 11-year-old boy who underwent decompression and drainage of a radicular cyst in deciduous tooth, followed by early orthodontic traction of permanent successor tooth with root dilaceration. The cyst healed successfully, and the impacted premolar was gradually aligned into the dental arch with favorable root development This case demonstrates that timely decompression of radicular cysts in deciduous teeth can effectively protect the successor permanent teeth. Meanwhile, for cases where permanent tooth impaction with root dilaceration has already occurred, timely orthodontic traction can move the root from the bone cortex into the cancellous bone to obtain growth space.